Central arterial stiffness and retinal vessel calibers: the Atherosclerosis Risk in Communities Study–Neurocognitive Study. Issue 2 (February 2020) - Meyer, Michelle L.; Klein, Barbara E.; Klein, Ronald; Palta, Priya; Sharrett, A. Richey; Heiss, Gerardo; Nambi, Vijay; Wong, Tien Y.; Tanaka, Hirofumi
Abstract : Background: The retinal microvasculature provides a window to the cerebral vasculature and enables examination of changes in retinal caliber that may mimic those occurring in cerebrovascular disease. The association of central arterial stiffness and retinal vessel caliber in a population sample is not fully understood. Methods: In 1706 older adults (mean age 76.3, 58.1% women) from the population-based Atherosclerosis Risk in Communities Study, we examined the cross-sectional association of central arterial stiffness [carotid–femoral pulse wave velocity (cfPWV)] with retinal vessel calibers [central retinal arteriolar equivalent (CRAE) and central retinal vein equivalent (CRVE)]. We estimated the association of cfPWV with CRAE narrowing (<25th percentile) and CRVE widening (>75th percentile) after adjustment for age, sex, race-field center, BMI, smoking, and type 2 diabetes. We tested for effect modification by sex, hypertension, and type 2 diabetes. Results: Carotid–femoral PWV (m/s) was not associated with the odds of CRAE narrowing [odds ratio (OR): 0.99; 95% CI: 0.95–1.03]. The association of cfPWV with CRVE widening was stronger in those without hypertension (OR: 1.10; 95% CI: 1.01–1.20) versus those with hypertension (OR: 1.01 95% CI: 0.96–1.05) and slightly stronger in those with type 2 diabetes (OR: 1.07; 95% CI: 1.00–1.14) versus without type 2 diabetes (OR: 1.01; 95% CI: 0.96–1.06). Conclusions: In older adults, cfPWV was associated with wider retinal venular caliber, particularly in individuals without hypertension. Central arterial stiffening may be associated with cerebral microvascular changes, as exhibited in its retinal vasculature component. Abstract : Supplemental Digital Content is available in the text